Inequality and agricultural structural change: Evidence from macro and microdata, 1950-present - Matthew Fisher-Post (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
Since 1950, agricultural productivity has been increasing even as labourers leave agriculture. However, while average productivity of the sector has been converging, within-sector inequality has been increasing. Agricultural income inequality is still less than overall income inequality, but it measures significantly higher when we use higher-quality and more comprehensive survey data. This means not only to observe the entirety of household farm income, but also to measure the magnitude of capital income and corporate profits in the sector. Given the likely increase in agricultural inequality during the process of structural change, I show also the extent to which social protection programmes are both insufficient and poorly targeted for rural populations.
Keywords: D3; N5; O1; Q1; 330; agricultural structural change; food systems transformation; inequality